The educator in the network (Journal of Parents and Teachers, 2014)
Searching for information is just one click away, but in many cases a single word can have 41,000 results; as a result, it is necessary to refine our search techniques.To do this, the article recommends using the search engines' own hierarchical "web directories". These act as an index, i.e. they provide a brief commentary on the information offered by a website and sometimes even an evaluation of the site.
Keywords: information search; ICT; online learning; the great six.